HEAD OF DEPARTMENT OF THE CRIMINAL, CRIMINAL PROCEDURE AND PENAL ENFORCEMENT AND FORENSIC OF THE INSTITUTE OF LEGISLATION OF REPUBLIC OF KAZAKHSTAN, CANDIDATE OF LEGAL SCIENCES, ASSOCIATE PROFESSOR - Karazhanov, Малик Дулатович; Kanatov , Алмас Канатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article analyzes the criminological characteristics of criminal offenses, encroaching on ecological safety in the context of the new Criminal Code of the Republic of Kazakhstan. The authors identified the main reasons for the ineffectiveness of the fight against criminal offenses, encroaching on ecological safety